Bi-enzymes treatments attenuate cognitive impairment associated with oxidative damage of heavy metals - Chen, Chao (R Soc Open Sci, 2021)
Oxidative stress has been implicated in the pathogenesis of cognitive impairment. Lead (Pb) is a common environmental toxicant and plays a vital role in oxidative stress activation. In this study, a superoxide dismutase (SOD) and catalase (CAT) containing poly (lactic-co-glycolic acid) (PLGA) meso-particles (PLGA@SOD-CAT) were prepared to attenuate cognitive impairment via inhibiting oxidative stress in rats. It was prepared using a double emulsion (water/oil/water phase) technique to minimize the hazardous effects of Pb burden on cognitive impairment. The meso-particles antagonized the Pb-induced cognitive impairments. Behaviour, serum biochemical parameters and biomarkers of oxidative stress in rats were evaluated after they were subjected to intravenous injection with lead nitrate and PLGA@SOD-CAT. Moreover, the potential protective mechanism of PLGA@SOD-CAT was determined. Notably, PLGA@SOD-CAT appreciably agented memory impairment caused by lead nitrate and it could significantly inhibit Pb-induced oxidative stress in the blood. Furthermore, a remarkable reversion effect of cognitive impairments, including escape latency, crossing platform times and time per cent during the platform quadrant, after PLGA@SOD-CAT administration were noted. Therefore, these results suggested that the bi-enzymes platform was a superior product in eliminating Pb-induced cognitive impairments through reducing expression of Pb-associated oxidative stress, and it could potentially be applied in detoxifying heavy metals in blood circulation.